Analisis Konsep Dasar Etika dan Profesi Keguruan di Era Society 5.0 - Dewi Afriyani Putri Siregar; Ismi Fahrunnisa; Rully Hidayatullah; Hadeli Hadeli; Hidayat Al-azmi (Lembag, 2025)
The Society 5.0 era demands that teachers adapt to technological advancements and the increasingly complex needs of society. Teachers are no longer just educators but also facilitators, mentors, and agents of change who can utilize technology in the learning process without abandoning human values. The teaching profession in this era emphasizes digital technology mastery, data literacy, creativity, and the development of students' character with a humanistic approach. This transformation aligns with the integration of technologies such as Artificial Intelligence (AI), the Internet of Things (IoT), and big data into social life. This study uses a descriptive qualitative approach through literature review to explain the core concepts of the teaching profession, required competencies, challenges faced, and strategies for implementing technology in education. Teachers in the Society 5.0 era must master four main competencies: pedagogical, personal, social, and professional, as outlined in national education policy. Major challenges include unequal access to technology, infrastructure readiness, and issues of digital ethics and security. Therefore, synergy between the government, educational institutions, and society is essential. Strategies such as project-based learning, the use of AI, and empathy-driven approaches are crucial to maintaining a balance between technological advancement and humanistic values in education.